Fiscal Policy Measures, Income Inequality and Health Outcomes of Countries in SSA - Akpa, Emeka; Adegbenro, Muiz (Acta Universitatis Danubius. Œconomica, 2023)
This study estimates the interactive effect of fiscal policy and government health expenditure on income inequality and health outcomes in Sub-Saharan Africa (SSA) countries. The study covers the period 2010–2022 using panel data on 12 countries. Estimation is done using the System GMM estimation technique. Findings from the estimated model shows that an interaction of fiscal policy and government health expenditure exerts a negative and significant effect on under-five mortality (MORT). On the other hand, the interaction of fiscal policy and government health expenditure leads to a reduction in life expectancy (LFX), but not significantly. Finally, the interaction of fiscal policy and government health expenditure leads to a negative effect on income inequality (INQ). Based on the findings, the study recommended that given that the interaction of both components of fiscal policy – income tax and government expenditure on health – and government health expenditure yields better outcomes on health and inequality (howbeit insignificant in the case of inequality), fiscal policy makers must ensure that there is no mis-match in the revenue and spending components of fiscal policy, and become more deliberate in channeling income tax to health spending